Impact of COVID-19 Related Lockdown on the Frequency of Acute and Oncological Surgeries—Lessons Learned From an Austrian University Hospital - Abram, Julia; Gasteiger, Lukas; Putzer, Gabriel; Spraider, Patrick; Mathis, Simon; Hell, Tobias; Martini, Judith (Frontiers in Public Health, 2021)
Innsbruck Medical University Hospital, Austria, provides the highest level of care for a region of approximately 1.8 million people. During the early COVID-19 outbreak in spring 2020 surgical activity was drastically reduced with the prime goal of preserving hospital capacities, especially intensive care beds. We conducted a retrospective analysis of surgical activities performed at Innsbruck Medical University Hospital during the lockdown period from March 15 to April 14, 2020 and compared these activities to the same period during the previous five years. Total surgical activity was reduced by 65.4% compared to the same period during the previous five years (p<0.001); elective surgeries were reduced by 88.7%, acute surgeries by 35.3% and oncological surgeries by 47.8% compared to the previous five years (all p<0.001). This dramatic decrease in acute and oncological surgeries can most likely be ascribed to the fact that many patients avoided health care facilities because of the strict stay-at-home policy and/or the fear of contracting SARS-CoV-2 in the hospital. In view of future waves, the population should be encouraged to seek medical help for acute symptoms and to attend cancer screening programs.